Equine arteritis virus gP5 protein induces apoptosis in cultured insect cells - Metz, German Ernesto (2014)
Equine Arteritis Virus (EAV) has been shown to induce apoptosis in vitro but the induction of this mechanism has not been previously associated with any viral gene product. In this work, we found a cytotoxicity effect of the EAV gP5 protein on baculovirus-insect cells and a low yield of protein recovery. Besides, different morphological features by electron transmission microscopy, DNA fragmentation in agarose gel, TUNEL analysis and caspase 3 activity were found. All these findings indicate that the EAV gP5 protein induces apoptosis in insect cells.